Increasing the ROI of Social Media Marketing - Mirchandani, Rohan; Kumar, V. (MIT Sloan Management Review, 2012)
With the growth of social media, influencing consumer preferences and purchase decisions through online social networks and word of mouth is an increasingly important part of every marketer's job. Companies such as Geico, Dell and eBay are adapting the traditional "one-way" advertising message and using it as a stepping-stone to begin a two-way dialogue with consumers via social media. Marketers know that theoretically, social media should be a powerful way to generate sustainable, positive word-of-mouth marketing. If marketers can only select the right social media platform, design the right message and engage the right users to spread that message, their campaign should be a success. But until now, that's been a big if. The authors propose a seven-step framework for success in social media marketing campaigns. Their framework involves identifying social media users who are not only influential but also particularly interested in the company's product or service category and then recruiting and incentivizing those influencers to talk about the company's product or service. The authors describe the implementation of their seven-step framework at Hokey Pokey Ice Cream Creations, an upscale ice-cream retailer with more than a dozen outlets across India. Hokey Pokey's social media campaign resulted in substantial increases in brand awareness, social media ROI and sales revenue growth rate for the company. The authors also explain three new metrics they developed for use in social media marketing campaigns: the Customer Influence Effect, which measures the influence a social media user has on other users in the network; the Stickiness Index, which helps identify social media users who actively discuss the company's product or service category; and Customer Influence Value, which helps measure the monetary gain or loss realized by a company in social marketing campaigns by accounting for an individual's influence on purchases by other customers and prospects.
Keywords: Social media; Social Media; Médias sociaux; social media